Advancements in micromotion-based fixation systems for fracture healing - Jiaxin Lv; Weichen Qi; Frankie Ka Li Leung (Journal of Orthopaedic Surgery)
Micromotion—defined as controlled cyclic axial movement at the fracture site—has emerged as a promising approach to enhance bone fracture healing. This review aims to evaluate micromotion-based fixation systems across biomechanical, preclinical, and clinical domains, highlighting their benefits, limitations, and technological progress. We summarize key micromotion technologies applied across various fixation systems, including far cortical locking and dynamic locking mechanisms in screws, suspension-based and shape-memory alloy-driven adjustments in plates, dynamization approaches in intramedullary nails through selective removal of interlocking components, and the evolution of external fixators from manually adjusted systems to intelligent, sensor-guided constructs such as the OrthoSpin frame.While internal fixations often rely on passive micromotion with limited controllability and potential safety concerns, external systems allow precise control but lack consensus on optimal stimulation parameters. Future advancements should focus on integrating real-time sensing and adaptive feedback to tailor micromotion based on healing stages and patient-specific needs.